Scalp Metastasis as the First Presentation of an Underlying Aggressive Pancreatic Cancer - Preethi Ramachandran MD; Lakshmi Boyapati MD; Gardith Joseph MD (SAGE Publishing, 2020)
Pancreatic ductal adenocarcinoma, an extremely aggressive cancer, has high metastatic potential. Cutaneous metastasis is very uncommon, representing only <10% of all cases, presenting mostly around the umbilical region. Non-umbilical metastasis is even rarer, and the significance remains unknown. In this article, we describe a case of a 76-year-old gentleman who initially presented with an asymptomatic scalp lesion, which on biopsy revealed metastatic adenocarcinoma of pancreatic origin. Detailed workup revealed extremely high tumor burden with metastases involving muscles, subcutaneous tissues, bone, lung, spleen, liver, and colon. Cutaneous involvement in pancreatic cancer represents poor survival with widespread dissemination of the disease. The involvement of some sites and not others and the extreme degree of aggressiveness might reflect subgroups of this cancer with different molecular biology. Identifying these groups may have utility in determining prognosis and stratifying treatment for patients. This will hopefully translate into better diagnostic tests and therapies in the near future.